2007
DOI: 10.1111/j.1365-2559.2007.02687.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of androgen receptor and two androgen‐induced proteins (apolipoprotein D and pepsinogen C) in ductal carcinoma in situ of the breast

Abstract: AR expression may represent an independent predictive factor in DCIS of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Similar to previous reports [38], Yu et al [39] reported significantly higher AR expression in DCIS adjacent to invasive ductal carcinoma (IDC) than in specimens of pure DCIS or IDC (93.9% vs 79.4% and 72.5%; P00.046 and P<0.001 respectively). Based on these results and a previous study by Hanley et al [40] that demonstrated a significant loss of AR expression between high-grade DCIS and high-grade IDC (93% vs 55%; P<0.0001), there is speculation that AR may play a role in tumor dissemination, invasion, and progression, but further investigation in this subgroup is necessary.…”
Section: Androgen Receptor As a Prognostic Biomarkersupporting
confidence: 74%
“…Similar to previous reports [38], Yu et al [39] reported significantly higher AR expression in DCIS adjacent to invasive ductal carcinoma (IDC) than in specimens of pure DCIS or IDC (93.9% vs 79.4% and 72.5%; P00.046 and P<0.001 respectively). Based on these results and a previous study by Hanley et al [40] that demonstrated a significant loss of AR expression between high-grade DCIS and high-grade IDC (93% vs 55%; P<0.0001), there is speculation that AR may play a role in tumor dissemination, invasion, and progression, but further investigation in this subgroup is necessary.…”
Section: Androgen Receptor As a Prognostic Biomarkersupporting
confidence: 74%
“…We speculate that local autocrine or paracrine androgen production is associated closely with the proliferation of AC, particularly in the early phases of tumour progression with a tendency toward stromal invasion. The difference in androgen synthesis in AC might explain why and how some AC lesions progress to massive invasion while other AC lesions remain in the non‐ or less‐invasive state 24 . In support of this hypothesis, there is evidence that AR/androgen up‐regulates MMPs, contributing to invasiveness via destruction of collagen IV 14,25 …”
Section: Discussionmentioning
confidence: 99%
“…IHC was performed with an indirect immunoperoxydase method using the Benchmark XT from Ventana. Two antibodies directed against AR (a rabbit monoclonal primary antibody, clone SP107, prediluted, Ventana) [17,18] and FOXA1 (an affinity purified goat polyclonal antibody, HNF-3α/β (C-20), Santa Cruz biotechnology, dilution 1/200e) [19][20][21][22] were tested on the 14 TMAs.…”
Section: • • Patientsmentioning
confidence: 99%